Climate Dynamics : Why Does Climate Vary?. - Sun, De-Zheng (Geophysical monograph, 2013)
Published by the American Geophysical Union as part of the Geophysical Monograph Series. Climate Dynamics: Why Does Climate Vary? presents the major climate phenomena within the climate system to underscore the potency of dynamics in giving rise to climate change and variability. These phenomena include deep convection over the Indo-Pacific warm pool and its planetary-scale organization: the Madden-Julian Oscillation, the monsoons, the El Niño-Southern Oscillation, the Pacific Decadal Oscillation, and the low-frequency variability of extratropical circulations. The volume a.